Practical Bioinformatics - Agostino, Michael J (Garland Science, 2013)
This guide is specifically designed for biology majors, with heavy emphasis on learning the steps necessary to perform bioinformatics analysis to answer biological questions. The chapters are focused on sequence analysis activities, a frequently performed subset of the field of bioinformatics.